Local Expertise the Baduy Indigenous Community as a Literacy Reference in The Millennium Era - Elis Suryani Nani Sumarlina; Rangga Saptya Mohamad Permana; Undang Ahmad Darsa; Ganjar Kurnia; Abdul Rasyad (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2023)
Every ethnic group has inherited local cultural wisdom from their predecessors. Similarly, the Sundanese people's riches include a wide range of great ideas, religious systems, and perspectives on life. This local wisdom can be utilized as a reference for the next generation, as it is still relevant to modern millennial life. One is related to the habits, traditions, and religious systems practiced by the Baduy traditional community. This indigenous wisdom is reflected in rituals and traditions that the community still follows and fiercely adheres to. This is inextricably linked to their belief system. Baduy society's beliefs are based on Sundanese Wiwitan teachings. The existence of these teachings is intimately related to the customs. This page also seeks to reveal the calculation and calendar system, which will serve as a reference and guideline for 'kolénjér' and 'literature' calculations. This study employs both descriptive analytical research methodologies and multidisciplinary cultural study methods, such as ethnography, social anthropology, communication, and oral traditions. The findings can disclose practices, traditions, religious systems, calculations, and calendars that have previously been hidden and unknown to individuals outside Baduy and are generally significantly different from other belief systems. The findings of this study can be used as a literacy resource for other scientific domains in a multidisciplinary context.